A system-level approach to single-molecule live-cell fluorescence microscopy - Harriman, O (2013)
In this work a system-level approach was taken to the single-molecule fluorescence microscopy of living cells. This primarily involved the unification of relevant information within appropriately structured artefacts that were used to inform and enhance experimentation. Initially the diversity of emerging single-molecule techniques was reviewed and presented with a novel article structure to suit the purpose of designing an experiment (Harriman and Leake 2011). Techniques were grouped by the type of information they could access, rather than the standard organisation centred on the techniques themselves. A bespoke microscope was conceived and built with reference to knowledge and tools from the fields of Architecture and Systems-Engineering. The microscope layout would enable multiple experiment types through independent control of multiple illumination beams. A technique was developed enabling the prescription of evanescent field penetration depth for each incident beam. The various empirical and theoretical results that are used to understand and modify a microscopy experiment were integrated into an internally consistent simulation model (Harriman and Leake. 2013). This was used to inform the selection of experimental components and parameters and ultimately acquire higher data quality as measured by functions such as signal-to-noise ratio (SNR). The combined experimental system of microscope and simulation model was applied in two live-cell investigations. In Escherichia coli, the spatial distribution of membrane bound proteins was investigated and a novel technique was applied to the analysis of colocalisation. Results indicate that NADH dehydrogenase and ATP synthase follow uncorrelated trajectories. This supports the hypothesis of spatial decoupling of molecules that energise the membrane and molecules that use membrane energy. In human carcinoma cells, the mechanism of ligand-receptor binding was investigated. Data was collected prior to and periodically after the addition of ligands, and fluorescence images were acquired of both ligands and receptors. Analyses based on single particle tracking are currently being carried out by a collaborator to extract information on stoichiometry and dynamics at the single-molecule level.